Molecular and epidemiological characterization of human adenoviruses infection among children with acute diarrhea in Shandong Province, China - Deyu Huang; Zheng Wang; Guanyou Zhang; Lintao Sai (Virology Journal, 2021)
Abstract Background Human adenovirus (HAdV) had been recognized as one of the most common enteric viruses associated with acute diarrhea in children. The present study was carried out to demonstrate the molecular and epidemiological characterization of HAdV Infections among children in Shandong province in China between July 2017 and June 2018. Methods Fecal specimens were collected from children under 5 years old with acute diarrhea. DNA was extracted from the stool specimens and adenovirus DNA was detected by PCR amplification with specific primers. The amplification products were subjected to electrophoresis and visualized on a UV transilluminator. All positive RT-PCR amplification products were sequenced and the obtained sequences analyzed by MEGA (version 7.0). Demographic information and clinical manifestation data were also analyzed. Results In total, 656 fecal specimens were collected and the overall positive rate of HAdV was 7.47%. HAdV infections were detected in all age groups, in which children aged 13–24 months presented the highest positive rate. Seasonal pattern could be observed with a peak in December, January and February. Diarrhea, vomiting, dehydration and fever were the main clinical manifestations, in which vomiting was the most common accompanied symptom. By phylogenetic analysis, four species (A, B, C, and F) were detected and seven different serotypes were identified. HAdV-41 (48.98%, 24/49) was the most common serotype followed by HAdV-3 (18.37%, 9/49), HAdV-31 (14.29%, 7/49), HAdV-7 (8.16%, 4/49), HAdV-40 (4.08%, 2/49), HAdV-1 (4.08%, 2/49) and HAdV-2 (2.04%, 1/49). Conclusion This study indicated that HAdV infection was an important cause of acute diarrhea among children under 5 years old in Shandong province. The results will contribute to (a) increase understanding of the role of HAdV in diarrheal children and enhance identification of the predominant diarrhea pathogen for diagnosis; (b) avoid abuse of antibiotics; (c) monitor the change of prevalent HAdV serotypes and promote vaccine development and vaccination.